Pembelajaran PKN pada Pendekatan Saintifik - Meylisa Cholissatun Fitri; Fanny Sasmitha; Nur Aisyah Perangin-angin; Syahrial Syahrial (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
The scientific approach is an approach that conveys students' understanding of knowledge and uses a scientific approach to understand the scientific approach that does not depend on direct information from the teacher, anytime, anywhere, anytime (Daryanto, 2015). Through this approach, learning is aimed at students who are centered on interactive, encouraging students to improve their thinking skills. According to Permendikbud (2013), students carry out five main activities to learn: observation, questioning, gathering information, connection and communication. When using a scientific approach, the question aspect is the most difficult aspect. Many students have low enthusiasm, curiosity, and motivation to follow the PPKN compartment. The area of ​​study is considered boring and student life is lost. Low skills in critical thinking, problem solving and decision making also interfere with the learning process (Fischer et al 2012 Murawski 2012 Wang & Zheng, 2016). To answer or ask questions, students must have the ability to analyze, evaluate, integrate, and apply acquaintances.